Preliminary in vitro antimicrobial screening of chemical constituents isolated from the root of Lepleae mayombensis (Meliaceae) - Lazare Sidjui Sidjuia & b & c, Yvan Anderson Ngandjui Tchangoued, Sindhu Radhakrishnanc, Perumal Karthigae, Paul Djomgoueh, Rufin Marie Kouipou Toghueof, Louis Claire Ndel Fameng, Gurumasy Annaduraic, Gabriel Ngosong Folefoc (Journal of Applied Pharmaceutical Science, 2015)
The Phytochemical study of Methanol/dichloromethane extract of root of Leplaea mayombenis led to the isolation and identification four limonoids: (8S,9R,10R,11S,13R,17R)-6,11-dihydroxy-14,15-epoxy-4,4,8,10,13-pentamethyl-17-(2-oxo-2,5-dihydrofuran-3-yl-)-11,12,13,15,16,17-hexahydro-4H-cyclopent[α] phenanthrene-3,7(8H,9H,10H,14H)-dione (1), (8S,9R,10R,11S,13R,17R)-6,11-dihydroxy-14,15-epoxy-4,4,8,10,13-pentamethyl -17-(23-methoxy-2-oxo-2,5-dihydrofuran-3-yl-)-11,12,13,15,16,17-hexahydro-4H-cyclopent [α] phenanthrene 3,7(8H,9H,10H,14H)-dione (2), (8S,9R,10R,11S,13R,17R)-6,11-dihydroxy-14,15-epoxy-17- ((s)-2-hydroxy-5-oxo-2,5-dihydrofurano-3-yl)-4,4,8,10,13-pentamethy-l,10,11,12,13,15,16,17-octahydro-4H-cyclopent [α] phenanthrene-3,7(8H,9H,10H,14H)-dione (3), 8S,9R,10R,11S,13R,17R)-1,6,11-trihydroxy-14,15-epoxy-17- [((2s)-2-hydroxy-5-oxo-2,5-dihydrofurano-3-yl)]-4,4,8,10,13-pentamethyl-l,10,11,12,13,15,16,17-octahydro-4H-cyclopent[α]phenanthrene-3,7(8H,9H,10H,14H)-dione (4), one cycloartane : 9,10-cyclopropyl-(3S,5R,8R,13R,14S,17R))-4,4,13,14,17-pentamethyl-l7-((2R,5S,6R)-5,6,7-trihydroxy-6-methylheptan-2-yl)-hexadecahydro-1H-cyclopentane[α]phenanthrèn-3-ol (5) and three steroids: β-sitosterol (6), stigmasterol (7) and stigmasterol 3-O-β-D-glucopyranoside (8). Their structures were elucidated on the basis of spectroscopic analysis and by comparison of their spectral data with those reported in the literature. To the best of our knowledge, all these compounds were isolated for the ï¬rst time from the Leplaea mayombensis. The antimicrobial studies showed that isolated compounds exhibit antimicrobial activity with inhibition zone diameters varying from 0.00 ± 0.00 to 29.00 ± 0.00 mm on both bacteria and fungi. 9,10-cyclopropyl-(3S,5R,8R,13R,14S,17R) )-4,4,13,14,17-pentamethyl-l7-((2R,5S,6R)-5,6,7-trihydroxy-6-methylheptan-2-yl)-hexadecahydro-1 H-cyclopentane[α] phenanthrèn-3-ol (5) was the most active against Escherichia coli (28.00±0.00 mm), Pseudomonas sp (27.00±0.00 mm), Lactobacillus acidophilus (29.00±0.00 mm), Streptococcus pneumonia (23.00±0.00 mm) and Serratia entomophili (29.00±0.00 mm), C. albicans (12±0.00 mm), and T. viridae (13±0.00 mm) The results from this study support the conclusion that L. mayombensis contain many classes of antimicrobial compounds and therefore justify their traditional usage in the treatment of infectious diseases.
Keywords: Leplaea mayombensis,Phytochemical study,Limonoids,Cycloartane,antimicrobial.